Structural, Morphological, and Electron Transport Studies of Annealing Dependent In2O3 Dye-Sensitized Solar Cell. (4th June 2015) - Mahalingam, S.; Abdullah, H.; Shaari, S.; Muchtar, A.; Asshari, I.
Abstract : Indium oxide (In2 O3 ) thin films annealed at various annealing temperatures were prepared by using spin-coating method for dye-sensitized solar cells (DSSCs). The objective of this research is to enhance the photovoltaic conversion efficiency in In2 O3 thin films by finding the optimum annealing temperature and also to study the reason for high and low performance in the annealed In2 O3 thin films. The structural and morphological characteristics of In2 O3 thin films were studied via XRD patterns, atomic force microscopy (AFM), field-emission scanning electron microscopy (FESEM), EDX sampling, and transmission electron microscopy (TEM). The annealing treatment modified the nanostructures of the In2 O3 thin films viewed through FESEM images. The In2 O3 -450°C-based DSSC exhibited better photovoltaic performance than the other annealed thin films of 1.54%. The electron properties were studied by electrochemical impedance spectroscopy (EIS) unit. The In2 O3 -450°C thin films provide larger diffusion rate, low recombination effect, and longer electron lifetime, thus enhancing the performance of DSSC.